Association of physical activity and feeding preferences of children with their nutritional status: A school based crosssectional study - Pant, Smriti; Vaidya, Abhinav (Journal of Kathmandu Medical College, 2022)
Background: People who are obese have a higher risk of acquiring many severe diseases. Feeding preferences and physical activities are deemed to play an important role in obesity in children. Objectives: This study aimed to find out the prevalence of over nutrition among primary level children in selected private schools of Kathmandu Metropolitan City (KMC). It also assessed the impact of physical activity level and feeding preferences on their nutritional status. Methods: An analytical cross-sectional study was done among 488 children and their parents, in six schools of KMC between May and August 2016. Children with written permission were included in the study, while absentees or hostel dwellers were excluded. Multistage cluster sampling was used for sampling. Ethical clearance was obtained from Institutional Review Committee of Kathmandu Medical College Public Limited and informed consent was taken from all participants. The questionnaire contained questions regarding socio-demographic details, modified Child’s Feeding Questionnaire and Child Physical Activity Questionnaire. Data was entered and analysed using SPSS v.20. Results: The prevalence of overweight was 4.5% (22) and obesity was 2.5% (12). Similarly, 135 (27.7%) children had adequate physical activity per day. Those with adequate physical activity were 1.5 times more likely to be overweight. Parent’s perception of their child’s weight and their concern about their child being overweight were both predictors of the child’s actual weight. Conclusion: Nutritional status of children was affected by feeding preferences of their parents, so they need to be educated about the importance of healthy eating and physical activities.